The feasibility of molecularly imprinted polymer as an additive in column filter to remove arsenic species in tertiary wastewater treatment - Nurlin, Abu Samah; Nurjannah, Salim; Siti Maznah, Kabeb (American Chemical Society, 2024)
Traditional methods of arsenic removal in tertiary wastewater treatment rely on complex chemical processes, which are often costly and environmentally unfavorable. Molecularly imprinted polymers (MIPs) are investigated as a sustainable and innovative column filter option for arsenic removal. This paradigm shift in tertiary wastewater treatment not only addresses the pressing issue of arsenic contamination but also offers a cost-effective and environmentally friendly solution. This letter emphasizes the critical necessity to add MIPs to column filters for arsenic removal and transforming tertiary wastewater treatment. MIPs will transform wastewater arsenic pollution prevention, protecting public health and the environment.